Anti-Mullerian Hormone Induces Foxo1 and Sirt1 Genes Expression in Mouse Ovary - Abouzeid, Hoda M.; Hashad, Ingy M.; Rady, Mona; Abdel-Maksoud, Sahar M. (Current Pharmaceutical Biotechnology, 2025)
BackgroundAnti-Mullerian hormone (AMH) plays a pivotal role in follicular growth and atresia. Recent studies highlighted the role of AMH in attenuating granulosa cell apoptosis and subsequent follicular atresia. Despite the raising understanding of the role of AMH in folliculogenesis, and its contribution to the pathophysiology of certain diseases such as polycystic ovary syndrome, the effect of AMH on the expression of genes regulating folliculogenesis is stills limited.ObjectiveThis study aims to gain insights into the effect of AMH on atresia regulating genes.MethodsIn vivo study was performed on C57BL/6J mice injected with AMH for one month. Thereafter, relative gene expression quantification of Foxo1, Sirt1, p53, Bim, and Bax genes were performed using RT-PCR.ResultsIn this study, AMH significantly enhanced the expression of Foxo1 and Sirt1 gene compared to the control group. On the contrary, AMH did not modulate the expression of p53, Bim, or Bax genes. AMH was also found to increase serum FSH and LH levels in a dose-dependent manner.ConclusionThis study demonstrated the capability of AMH to induce Foxo1 and Sirt1 genes. Moreover, our study revealed the role of AMH in elevating LH serum level which is a main contributor to the pathophysiology of polycystic ovary syndrome, opening new avenues for the study of AMH as a main contributor to the stalled follicular atresia and growth associated with the disease.
Keywords: Bax